An Evaluation of the Self-Reported Knowledge Base of Disaster Management Core Competencies of Australian Paramedics. Issue Volume 34:Issue s1(2019) (May 2019) - Horrocks, Peter; Tippett, Vivienne; Aitken, Peter
Abstract : Introduction: Evidence-based training and curriculum are seen as vital in order to be successful in preparing paramedics for an effective disaster response. The creation of broadly recognized standard core competencies to support the development of disaster response education and training courses for general health care providers and specific health care professionals will help to ensure that medical personnel are truly prepared to care for victims of mass casualty events. Aim: To identify current Australian operational paramedic's specific disaster management education and knowledge as it relates to disaster management core competencies identified throughout the literature and the frequency of measures/techniques which these paramedics use to maintain competency and currency. Methods: Paramedics from all states of Australia were invited to complete an anonymous online survey. Two professional bodies distributed the survey via social media and a major ambulance service was surveyed via email. Results: The study population includes 130 respondents who self-identified as a currently practicing Australian paramedic. Paramedics from all states except South Australia responded, with the majority coming from Queensland Ambulance Service (N= 81%). In terms of experience, 81.54% of respondents report being qualified for greater than 5 years. Initial analysis shows that despite the extensive experience of the practitioners surveyed when asked to rate from high to low their level of knowledge of specific disaster management core competencies a number of gaps exist. Discussion: Core competencies are a defined level of expertise that is essential or fundamental to a particular job, and serve to form the foundation of education, training, and practice for operational service delivery. While more research is needed, these results may help inform industry, government, and education providers to better understand and to more efficiently provide education and ongoing training to paramedics who are responsible for the management of disaster within the Australian community.